Clinical Pelvimetry Before and During Labour: A Comparative Study amongst Nulliparous Women - Shresth, Junu; Pradhan, Neelam; Rana, Ashma (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v4i2.5044 NJOG 2010 Jan-Feb; 4(2): 32-39